2003
DOI: 10.1037/0096-3445.132.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Memory organization of action events and its relationship to memory performance.

Abstract: Previous research yielded inconsistent results regarding the memory organization of self-performed actions. The authors propose that task performance changes the very basis of memory organization. Enactment during study and test (Experiment 1) yielded stronger enactive clustering (based on motor-movement similarities), whereas verbal encoding yielded stronger conceptual clustering (based on semantic-episodic similarities). Enactment enhanced memory quantity and memory accuracy. Both measures increased with ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 92 publications
(169 reference statements)
3
32
1
Order By: Relevance
“…Our performance test replicated the finding that organization is sometimes superior after enactment than after verbal learning (Koriat & Pearlman-Avnion, 2003). Those authors attributed it to motor information.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our performance test replicated the finding that organization is sometimes superior after enactment than after verbal learning (Koriat & Pearlman-Avnion, 2003). Those authors attributed it to motor information.…”
Section: Discussionsupporting
confidence: 79%
“…actions are indeed not organized according to semantic categories (such as gardening or cooking), but to bodymovement similarity (such as twisting and covering) (Koriat & Pearlman-Avnion, 2003). These findings were interpreted as evidence for the motor-code view (also see Hornstein & Mulligan, 2004, for a recent interpretation of findings in line with that account).…”
Section: Melanie C Steffenssupporting
confidence: 60%
See 1 more Smart Citation
“…The nervous system from the spinal cord up is divided into afferent and efferent processes, but in modern-day views of episodic memory, efferent processes are typically neglected except in work on embodied cognition and the role of enactment in memory (Engelkamp, 2001;Glenberg, 1997;Koriat & Pearlman-Avnion, 2003;Zimmer et al, 2001). This neglect of efferent processes is reasonable when the tie between memories and the way they are expressed motorically is arbitrary (e.g., expressing "yes" by pressing a button, speaking, writing, or nodding).…”
Section: Motor Outputmentioning
confidence: 99%
“…A number of published reports have shown consistent enactment effects in free recall without any exceptions (e.g., Earles & Kersten, 2000Earles, Kersten, Turner, & McMullen, 1999;Engelkamp, Seiler, & Zimmer, 2004;Engelkamp & Zimmer, 1996Helstrup, 2004;Knopf, 1995a;Koriat & Pearlman-Avnion, 2003;Norris & West, 1993;Ratner & Hill, 1991;von Essen, 2005;Zimmer, 1991;Zimmer, Helstrup, & Engelkamp, 2000). However, other studies have reported at least one exception-that is, one experiment or condition in which no enactment effect in free recall emerged (Brooks & Gardiner, 1994;Daprati, Nico, Saimpont, Franck, & Sirigu, 2005; Engelkamp, Mohr, & Zimmer, 1991;Foley, Bouffard, Raag, & DiSanto Rose, 1991;Helstrup, 1996Helstrup, , 2005Helstrup & Molander, 1996;Knopf, 1995b;Knopf, Mack, Lenel, & Ferrante, 2005;Mohr, Engelkamp, & Zimmer, 1989;Zimmer & Engelkamp, 1985, 1989.…”
mentioning
confidence: 89%